IMPROVEMENT OF STUDENTSâ INTEREST IN SOCIOLOGY COURSES, AT SMA NEGERI 1 BANDAR PETALANGAN, PELALAWAN, RIAU - Hardinata, Amrizal; Melia, Yenni; Rahmad, Darmairal (Pendidikan Sosiologi, 2014)
The studentsâ interest to the sociology subject can be told lower, it can be seen form the teaching process where some of student disturb their friend in teaching and while teacher explaing the subject in fron of the class, student did not pay attention, write teacherâs explanation thus in their examination a lot of them was unable answer the question was given by teacher. The formulation of this research was how the improvement of studentsâ interest in sociology teaching at SMAN 1 Bandar Petalangan. This research aim to describe the improvement of studentsâ interest in sociology teaching at SMAN 1 Bandar Petalangan of Pelalawan Regency, Riau. The type of this research was descriptive by using qualitative method. As for the informant of this research was sociology teachers. Method of collection the data used observation, interview and documentation. The collecte data was analyzed by doing the reduction data, interpretating data and drawing the conclusion. The result of research depicted that the imrovement of studentsâ interest in learning sociology at SMAN 1 Bandar Petalangan of Pelalawan Regency Riau were a) teacher in reaching the studentsâ interest in learning by using discusion method. The student felt interest following the teaching-learning processÂ  by disuction method due to have freedom in giving opinion and idea. b) teacher in reaching the studentsâ happiness in learning by using picture media. c) In the discussion the teacher used printed media. d) teacher in doing to improve studentsâ awareness in learning by changing the teaching method by giving individual assignment.